1983
DOI: 10.1111/j.1348-0421.1983.tb00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bordetella pertusiss Components on IgE and IgG1 Responses

Abstract: The effect of dermonecrotic toxin (DNT), fimbrial hemagglutinin (FHA), K-agglutinogen, lipopolysaccharide (LPS), and pertussigen from Bordetella pertussis on the production of IgE and IgGI antibodies to hen egg albumin (Ea) was investigated in C57BL/6 mice. The IgE antibody contents were determined by passive cutaneous anaphylaxis (PCA) in the skin of Lewis rats, while the IgG I antibody contents were determined by PCA reactions on the skin of mice using sera that had been heated for 3 hr at 56 C to destroy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This is probably due to the presence of transplacentally acquired antibody to PT. PT is a strong adjuvant in several immunologic systems in several animals and humans (14,15,190,235,246,452,453,456,553,561,573,575,578,600,610,649,699,745,746,801,804). This adjuvancy in the experimental-animal model is associated with enhancement of serum antibody responses to other antigens, increased cellular immune responses to various protein antigens, contribution to hyperacute experimental autoallergic encephalomyelitis, and increased anaphylactic sensitivity.…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…This is probably due to the presence of transplacentally acquired antibody to PT. PT is a strong adjuvant in several immunologic systems in several animals and humans (14,15,190,235,246,452,453,456,553,561,573,575,578,600,610,649,699,745,746,801,804). This adjuvancy in the experimental-animal model is associated with enhancement of serum antibody responses to other antigens, increased cellular immune responses to various protein antigens, contribution to hyperacute experimental autoallergic encephalomyelitis, and increased anaphylactic sensitivity.…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…If administered a few days before or after antigen, B. pertussis may actually suppress the response. PT preparations have also been reported to augument antibody responses and are particularly effective in priming for enhanced secondary responses (28,33). However, like the B. pertussis whole-cell vaccine, toxin preparations can also markedly suppress antibody responsiveness if the timing of adjuvant and antigen is varied (2,14).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, this vaccine enhances immunoglobulin G (IgG) and IgE antibody responses (27,39). Extracts of B. pertussis enriched in PT activity also augment IgG and IgE antibody responses (24,28,33); however, similar preparations have also been reported to suppress antibody formation. Asakawa (2) demonstrated that the primary antibody responses to either sheep erythrocytes (SRBC) or tetanus toxid were suppressed in mice pretreated with PT.…”
mentioning
confidence: 99%
“…In particular, chemically inactivated B. pertussis has been recognized for years to act as a potent adjuvant of different vaccine preparations [77][78][79]. In the last few years it has become clear that the adiuvanticity of B. pertussis vaccine (composed of chemically inactivated bacteria) and PTX is essentially associated with the nontoxic component of PTX [80,81].…”
Section: Adjuvant Properties Of Ptx and Ptx-bmentioning
confidence: 99%